Radiofrequency Ablation and Intrauterine Transfusion in a Delayed Diagnosed Acardiac Twin Pregnancy - Fatemeh Rahimi-Sharbaf; Mahboobeh Shirazi; Kamran Hessami; Maasoumeh Saleh; Fatemeh Golshahi; Sara Saeedi; Abolfazl Shirdel Abdolmaleki; Seyede Houra Mousavi Vahed; Behnaz Nouri; Behrokh Sahebdel (Hindawi Limited, 2023)
Twin reversed arterial perfusion (TRAP) sequence or acardiac twin is a rare and severe complication of monochorionic multiple pregnancies. Acardiac twin accounts for 10% of all TRAP sequences, which is the most morphologically developed acardius. We present an undiagnosed TRAP sequence case up to 24 weeks of gestation who underwent successful amnioreduction, radiofrequency ablation (RFA), and intrauterine transfusion (IUT). During follow-up, hydrops of surviving co-twin disappeared, and fetal heart function improved. Finally, a healthy girl weighing 2400 g was born at 36 weeks of gestation. To our knowledge, this is the first reported acardiac twin pregnancy, which requires IUT, in addition to RFA, due to late diagnosis. Therefore, this case report presents successful management options for TRAP sequence cases diagnosed late in pregnancy.